Epidemiology and Control Measures of Helminth Parasites in Small Ruminants - Chamuah, J. K.; Perumal, P.; Mech, A. (International Journal of Bio-resource and Stress Management, 2013)
Epidemiology of parasitic disease is very important for control as well as preventive measures in small ruminants. The precipitating factor of environment and host parasite plays a very important role for prevalence and occurrence of parasites in population. Hence, a systematic approach and judicious use of anthelmintic will not only help in substantial control of parasite in population but also increase productivity of animals. However, recent advancement of biological control and immunological control will be promising hope for reduce morbidity and mortality due to gastrointestinal parasites. The elucidation of parasitic antigen will be of great help in developing of successful vaccine in near future.